Why Didn't the College Premium Rise Everywhere? Employment Protection and On-the-Job Investment in Skills - Matthias Doepke; Ruben Gaetani (Institute of Labor Economics (IZA), 2020)
Why has the college wage premium risen rapidly in the United States since the 1980s, but not in European economies such as Germany? We argue that differences in employment protection can account for much of the gap. We develop a model in which firms and workers make relationship-specific investments in skill accumulation. The incentive to invest is stronger when employment protection creates an expectation of long-lasting matches. We argue that changes in the economic environment have reduced relationship-specific investment for less-educated workers in the United States, but not for better-protected workers in Germany.
Keywords: E24; J24; J31; O15; 330; college wage premium; employment protection; job-specific skills